Flicker-defined form perimetry in glaucoma patients - Horn, Folkert; Kremers, Jan; Mardin, Christian Y.; Jünemann, Anselm; Adler, Werner; Tornow, Ralf-Peter (Graefes Archive For Clinical and Experimental Ophthalmology, 2015)
To assess the potential of flicker-defined form (FDF) perimetry to detect functional loss in patient groups with beginning glaucoma, and to evaluate the dynamic range of the FDF stimulus in individual patients and at individual test positions.FDF perimetry and standard automated perimetry (SAP) were performed at identical test locations (adapted G1 protocol) in 60 healthy subjects and 111 glaucoma patients. All patients showed glaucomatous optic disc appearance. Grouping within the glaucoma cohort was based on SAP-performance: 33 "preperimetric" open-angle glaucoma (OAG) patients, 28 "borderline" OAG (focal defects and SAP-mean defect (MD) <2 dB), 33 "early" OAG (SAP-MD < 5 dB), 17 "advanced" OAG. All participants were experienced in psychophysical and perimetric tests. Defect values and the areas under receiver operating characteristic curves (ROC) in patient groups were statistically compared.The values of FDF-MD in the preperimetric, borderline, and early OAG group were 2.7 ± 3.4 dB, 5.5 ± 2.6 dB, and 8.5 ± 3.4 dB respectively (all significantly above normal). The percentage of patients exceeding normal FDF-MD was 27.3 %, 60.7 %, and 87.9 % respectively. The age-adjusted FDF-mean defect (MD) of the G1X-protocol was not significantly correlated with refractive error, lens opacity, pupil size, or gender. Occurrence of ceiling effects (inability to detect targets at highest contrast) showed a high correlation with visual field losses (R = 0.72, p < 0.001). Local analysis indicates that SAP losses exceeding 5 dB could not be distinguished with the FDF technique.The FDF stimulus was able to detect beginning glaucoma damage. Patients with SAP-MD values exceeding 5 dB should be monitored with conventional perimetry because of its larger dynamic range.
EVALuna2:5485